Deuteration effects in the thermal conductivity of molecular glasses - Krivchikov, A.I.; Bermejo, F.J.; Sharapova, I.V.; Korolyuk, O.A.; Romantsova, O.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The thermal conductivity κ(T) of pure deuterated ethanol has been measured under its equilibrium vapor pressure in its orientationally-ordered crystal (T = 2 K – Tm), orientational glass and the glass state (T = 2 K – Tg, Tg is the glass transition temperature) solid phases. The temperature dependence of the conductivity is well described by a sum of two contributions: κ(T) = κI(T) + κII(T), where κI(T) account for the heat transport by acoustic phononsand κII(T) for the heat transfer by localized high-frequency excitations respectively. The thermal conductivities of deuterated and hydrogenated ethanols are compared in different phases. The phonon scattering mechanisms in the glasses have been analyzed. In the investigated glasses the effect of complete deuteration shows up asa contribution κII(T).